2015
DOI: 10.1007/s00442-015-3508-y
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific differences in plant chemotype determine the structure of arthropod food webs

Abstract: It is becoming increasingly appreciated that the structure and functioning of ecological food webs are controlled by the nature and level of plant chemicals. It is hypothesized that intraspecific variation in plant chemical resistance, in which individuals of a host-plant population exhibit genetic differences in their chemical contents (called 'plant chemotypes'), may be an important determinant of variation in food web structure and functioning. We evaluated this hypothesis using field assessments and plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 39 publications
3
40
1
Order By: Relevance
“…Bottom‐up effects mediated by intraspecific variation among plants can arise through various genetically based traits leading, for example, to differences in plant growth habit or metabolic diversity (Bálint et al, ; Johnson, ; Johnson & Agrawal, ; Kareiva & Sahakian, ; Mooney & Agrawal, ; Williams & Avakian, ; Züst & Agrawal, ; Zytynska & Weisser, ). Host‐plant biochemistry is a key factor in affecting herbivore performance and often mediates herbivore preferences (Bernays & Chapman, ; Karban & Baldwin, ; Rosenthal & Berenbaum, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bottom‐up effects mediated by intraspecific variation among plants can arise through various genetically based traits leading, for example, to differences in plant growth habit or metabolic diversity (Bálint et al, ; Johnson, ; Johnson & Agrawal, ; Kareiva & Sahakian, ; Mooney & Agrawal, ; Williams & Avakian, ; Züst & Agrawal, ; Zytynska & Weisser, ). Host‐plant biochemistry is a key factor in affecting herbivore performance and often mediates herbivore preferences (Bernays & Chapman, ; Karban & Baldwin, ; Rosenthal & Berenbaum, ).…”
Section: Introductionmentioning
confidence: 99%
“…Plants use these volatile compounds for direct defence (Martin & Bohlmann, ) or for internal, intra‐ or interspecific communication (e.g., Riedlmeier et al, ) as well as for communicating with higher trophic levels (reviewed in de Vos & Jander, ; Holopainen & Blande, ; Paré & Tumlinson, ). One example is the recruitment of predators or parasitoids by herbivore‐infested plants (plant–natural enemy–herbivores; e.g., Bálint et al, ; Linhart, Keefover‐Ring, Mooney, Breland, & Thompson, ; Ninkovic, Al Abassi, & Pettersson, ). Some herbivore species (Erb & Robert, ; Goodey, Florance, Smirnoff, & Hodgson, ; Opitz & Müller, ; Prudic, Khera, Sólyom, & Timmermann, ) have also evolved to take advantage of host‐plant‐derived secondary metabolites (including nonvolatile defensive compounds, e.g., salicin derivatives or glucosinolates, and volatile defensive compounds, e.g., benzaldehyde) to use them in their own defence strategies against predation (Dyer, ; Gauld, Gaston, & Janzen, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aphids interact with their tending ant species, with other specialised tansy aphid species and the myriad of natural enemies to form a metacommunity. Previous work242728 has shown that tansy chemotypes dominated by camphor, β-thujone, artemisia ketone and borneol can influence the community of associated invertebrates1829. However, many of these studies classified the plants into chemotypes based on the dominant terpenes, yet often it is the whole ‘blend’ of a plant’s emitted terpenes that has been found to influence plant-insect interactions30.…”
mentioning
confidence: 99%
“…Distinct chemotype preferences between predators were also detected. Aphid‐specialist seven‐spotted ladybirds, C. septempunctata were more often found on Camphor‐containing plants, while significantly higher numbers of the polyphagous nursery web spider Pisaura mirabilis Clerk (Arachnida: Araneae: Pisauridae) were observed on Borneol‐containing plants (Bálint et al, ). Furthermore, Clancy et al .…”
Section: Categories Of Specialismsmentioning
confidence: 99%